CASE SERIES OF CONGENITAL HYPERINSULINISM IN A TERTIARY MEDICAL CENTER - Rajendran, Sharmila Devi; Nuran, Arini; Hong, Janet Yeow Hua; Selveindran, Nalini M (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Congenital hyperinsulinism (CHI) is the most common cause of persistent hypoglycemia in infants and children. Early and appropriate recognition and treatment of hypoglycemia is vital to minimize neurocognitive impairment. This case series is to study the molecular diagnosis, medical management and outcome of children with CHI. METHODOLOGY Medical data of 17 patients who were diagnosed with CHI from 2008–2024 in Hospital Putrajaya was retrieved from a medical electronic report. RESULT Hypoglycaemia occurred within the neonatal period in 70% of patients. The remaining 30% presented at infancy with the oldest age of presentation at 11 months. The highest glucose infusion rate required was 20 mcg/kg/min. Genetic test was done for 11 patients. Of these, 54.5% of patients had ABCC8 mutation while 9% had GLUD1 and KCNJ11 gene mutation each. Gene testing was negative in 27%. In this cohort, 78.5% were responsive to diazoxide therapy, and the involved genes were ABCC8 and GLUD1. All patients who were diazoxide non-responders responded to octreotide therapy. The genes involved were ABCC8 (80%) and KCNJ11 (20%) mutation. Neurocognitive evaluation revealed developmental delay in 11% (n=2) of patients. CONCLUSION Identification of the etiology of CHI helps guide management decisions. Prompt and effective management of patients is critical to ensure a good quality of life and neurological outcome. Molecular genetic study is useful in the management of CHI and effective management with good compliance must be ensured.